Assessing temporal and spatial trends in estuarine nutrient dynamics using a multi-species stable isotope approach. (August 2016) - van de Merwe, Jason P.; Lee, Shing Yip; Connolly, Rod M.; Pitt, Kylie A.; Steven, Andy D.L.
Highlights: δ 15 N and δ 13 C of multiple species were used to assess spatial-temporal trophodynamics in an urban estuary. Phytoplankton indicates within estuary and seasonal differences in nutrient inputs. Prawns indicate between estuary and seasonal differences in nitrogen inputs. Fish indicate between estuary differences in carbon and nitrogen inputs. The multi-species approach reveals spatial-temporal differences in estuarine nutrient dynamics. Abstract: Coastal urbanisation can alter estuarine nutrient dynamics through the input of point-source and diffuse pollutants, and nutrient concentrations can be highly influenced by seasonal and episodic rainfall and river flow. Understanding of both the spatial and temporal variability of nutrient dynamics is therefore critical to managing these estuaries. This can be achieved by periodically analysing the stable isotopes a range of aquatic taxa with variable nutrient turnover rates, mobility and distribution within the estuary. In two subtropical urban estuaries with different land use patterns, we analysed the carbon and nitrogen stable isotopes of phytoplankton, shrimp, prawns and fish at various proximities to pollution sources in dry and wet seasons. The fast nutrient turnover rates and ubiquity of phytoplankton in the estuary resulted in stable isotopes varying over fine-scale spatial scales, particularly in relation to proximity to point-source pollution. The slower nutrient turnover rates and localised habitat use of prawns, resulted in stable isotopes varying over larger spatial (between pollution sources) and temporal (seasonal) scales. The much slower nutrient turnover rates and high mobility throughout the estuary of fish resulted in stable isotopes varying over very large-scale spatial scales (between estuaries). These results illustrate a wide range of spatial and temporal changes to estuarine nutrient dynamics in subtropical urban estuaries in relation to rainfall conditions and nutrient inputs. This research also highlights the application of stable isotopes in assessing estuarine trophodynamics, and provides direction on the types of organisms that should be used to assess different spatial and temporal trends.